Critical Insights of Customer Valuation Methods in the Relationship Marketing Paradigm - Rytel, Tomas (Ekonomika, 2006)
This paper is aimed at providing the key critical insights into the traditional customer valuation models RFM, FRAC and CLV in the context of relationship marketing. It examines the principal assumptions that have conditioned changes in the traditional approach to customer value measurement methods through the application of post-modern marketing (e.g., interactive, relationship, etc.) under the knowledge economy conditions. Although customer value can be examined using both quantitative and qualitative criteria (e.g., customer impact on public opinion, customer trust in the company, etc.), this paper treats customer value as a quantitative measure which is studied using different measurable qualitative indicators rather than analysing psychological, social and other types of qualitative criteria characterising the buyer/seller relationships. The analysis of the RFM, FRAC and CLV customer value measurement methods and of their variables is based on the methodology for the analysis and systematisation of the content of scientific and methodological literature to distinguish the key critical aspects of customer value measurement methods through the application of the principles characteristic of relationship marketing. The overview of customer value measurement methods provided in the paper does not purport for detailed research, which requires a profound study on the subject.